Analisis Pengaruh Utang Negara terhadap Pertumbuhan Ekonomi Indonesia Periode 2004-2023 Berdasarkan Data LKPP - Amelita Oktaviana; Ascaryan Rafinda; Oman Rusmana (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This research aims to analyze the influence of state debt on Indonesia's economic growth in the period 2004 to 2023 using data from the Central Government Financial Report (LKPP). State debt is often considered as an instrument for financing development, but there is the potential for negative impacts if its management is not optimal. This research uses a linear regression method to examine the relationship between state debt levels and Indonesia's economic growth during the specified period. The research results show that state debt has a significant influence on Indonesia's economic growth, with an important role in financing development but also has the potential to increase the economic burden if not managed well. This research provides policy recommendations for managing state debt to support sustainable economic growth.